ASKAP Observations of the Radio Shell in the Composite Supernova Remnant G310.6-1.6 - Wenhui Jing; Jennifer L. West; Xiaohui Sun; Wasim Raja; Xianghua Li; Lingxiao Dang; Ping Zhou; Miroslav D. Filipović; Andrew M. Hopkins; Roland Kothes; Sanja Lazarević; Denis Leahy; et al. (The Astrophysical Journal)
We report the observations of the radio shell of the supernova remnant (SNR) G310.6–1.6 at 943 MHz from the Evolutionary Map of the Universe (EMU) and the Polarization Sky Survey of the Universe’s Magnetism (POSSUM) surveys by using the Australian Square Kilometre Array Pathfinder (ASKAP). We detect polarized emission from the central pulsar wind nebula (PWN) with rotation measures varying from –696 rad m ^−2 to –601 rad m ^−2 . We measure the integrated flux density of the shell to be 36.4 ± 2.2 mJy at 943 MHz and derive a spectral index of α _pwn  = −0.4 ± 0.1 for the PWN and α _shell  = −0.7 ± 0.3 for the SNR shell. From the combined radio and X-ray observations, the object can be identified as a supernova explosion of about 2500 yr ago with an energy of about 1.3 × 10 ^50 erg, suggesting an ejected mass of about 10 M _⊙ . The circular radio shell outside the circular hard X-ray shell is unique among Galactic SNRs. We discuss several possible scenarios, including blast wave, reverse shock, and pulsar-fed emission, but find that none of them can fully explain the observed characteristics of the shell. This poses a challenge for understanding the evolution of SNRs. The results of this paper demonstrate the potential of the ASKAP EMU and POSSUM surveys to discover more objects of small angular size and low surface brightness.